Effect of idiopathic epiretinal membrane on macular ganglion cell complex measurement in eyes with glaucoma - Nakakura, Shunsuke; Asaoka, Ryo; Oogi, Satomi; Aoki, Ryota; Terao, Etsuko; Ueda, Kanae; Kiuchi, Yoshiaki (Frontiers in Medicine, 2022)
Background/Objectives: Co-existing idiopathic epiretinal membrane (ERM) and glaucoma complicate the estimation of glaucoma severity via optical coherence tomography. We investigated the effect of ERM and a new associated parameter, SUKIMA (space between the ERM and retinal surface), on ganglion cell complex (GCC) thickness in eyes with glaucoma, based on a matched comparison of visual field defects. Subjects/Methods: We retrospectively recruited 41 eyes from 34 glaucoma patients with idiopathic ERM and 41 eyes from 41 glaucoma patients without ERM as controls (matched by age, axial length, and mean visual field deviation). The thicknesses of GCC layers (retinal nerve fiber layer [RNFL], ganglion cell layer + inner plexiform layer [GCIPL], and GCC [RNFL + GCIPL]) were measured with swept-source optical coherence tomography. We investigated the presence of SUKIMA and its effect on GCC measurements. Results: RNFL, GCIPL, and GCC were thicker in ERM (+) eyes than in control eyes (31.0 ± 12.3 μm vs. 22.7 ± 10.8 μm, 62.6 ± 12.2 μm vs. 53.8 ± 5.9 μm, and 91.8 ± 16.6 μm vs. 76.8 ± 13.3 µm, respectively; P < 0.01). Eyes in the ERM-associated SUKIMA (+) group had thicker GCIPL and GCC than those in the ERM-associated SUKIMA (−) and control groups (P < 0.01). Conclusion: ERM-associated SUKIMA affects GCC thickness and can result in underestimations of glaucoma severity. We should check for the presence of ERM using a B mode scan as well as check for the SKIMA sign.